Using evidence to influence policy: Oxfam’s experience - Mayne, Ruth; Green, Duncan; Guijt, Irene; Walsh, Martin; English, Richard; Cairney, Paul (Palgrave Communications)
Policymaking is rarely ‘evidence-based’. Rather, policy can only be st rongly evidence-informed if its advocates act effectively. Policy theo ries suggest that they can do so by learning the rules of political sy stems, and by forming relationships and networks with key actors to bu ild up enough knowledge of their environment and trust from their audi ence. This knowledge allows them to craft effective influencing strate gies, such as to tell a persuasive and timely story about an urgent po licy problem and its most feasible solution. Empirical case studies he lp explain when, how, and why such strategies work in context. If anal ysed carefully, they can provide transferable lessons for researchers and advocates that are seeking to inform or influence policymaking. Ox fam Great Britain has become an experienced and effective advocate of evidence-informed policy change, offering lessons for building effecti ve action. In this article, we combine insights from policy studies wi th specific case studies of Oxfam campaigns to describe four ways to p romote the uptake of research evidence in policy: (1) learn how policy making works, (2) design evidence to maximise its influence on specifi c audiences, (3) design and use additional influencing strategies such as insider persuasion or outsider pressure, and adapt the presentatio n of evidence and influencing strategies to the changing context, and (4) embrace trial and error. The supply of evidence is one important b ut insufficient part of this story.